(untitled) (Journal of School Administration Research and Development, 2018)
The purpose of this study was to analyze selected variables for public schools and districts in Virginia to determine the relationship of school and policy characteristics to teacher absences. This study included two research questions: What is the relationship between certain school district policy provisions and teacher absenteeism? What is the relationship between certain school characteristics and teacher absenteeism? The analysis for this study involved computing descriptive statistics, correlating continuous variables, and running multiple regressions for each dataset (school and district for each year) to determine the predictors of the dependent variable, chronically absent teachers. Although the school models were significant, neither was a particularly strong predictor of chronically absent teachers, only accounting for 15.2% of the variation (2011-2012 model with R2 = .152) and 9.6% of the variation (2013-2014 model with R2 = .096) that is predicted by the independent variables. Nevertheless, there were independent policy and school variables that were significant predictors in both school years. The most prominent variables included total leave, personal leave maximums, income protection provisions (sick leave banks, short-term disability), free and reduced lunch population percentage of a school, pupil/teacher ratio of the school, and the grade level of the school (elementary, middle, and high).